Going the distance Eurasian trade and the rise of the business corporation, 1400-1700 - Harris, Ron 1960- (Princeton economic history of the Western world, 2020)
Long-distance oceanic and overland trade along the Eurasian landmass in the 1400s was largely dominated by Chinese, Indian, and Arabic traders and predominantly conducted over short trajectories by sole traders or organized around small-scale enterprises. Yet, within two centuries of Europeans' arrival in the Indian Ocean in 1498, long-distance trade throughout Eurasia was mainly taken over by them. By 1700, they had formed new, large-scale, and impersonal organizations, primarily a joint-stock business corporation between English East India Company (EIC) and Dutch East India Company (VOC). This allowed them to transform trade from an enterprise dominated by many small traders moving goods over short segments to a vertically integrated firm that was able to control goods from their origin to the end consumers. This rise of the business corporation proved essential for the economic rise of Europe. Why did the corporation arise indigenously only in Europe, and given its effective organization of long-distance trade, why wasn't it mimicked by other Eurasian civilizations for 300 years? Harris closely examines the role played by forms of organization in the transformation of Eurasian trade between 1400 and 1700, comparing the organizational forms that were used in four major civilizations: Chinese, Indian, Middle Eastern, and Western European. Through this comparative perspective, he argues that the organizational design of the EIC and VOC, the first long-lasting joint-stock corporations, enabled large-scale multilateral impersonal cooperation for the first time in human history. He also argues that this new organizational form enabled the English and Dutch to deploy more capital, more ships, more voyages, and more agents than other organizational forms